A Privacy-Preserving Scheme for Managing Secure Data in Healthcare System - Hamed, Naba M.; Yassin, Ali A (Iraqi Journal for Electrical and Electronic Engineering, 2023)
In the world of modern technology and the huge spread of its use, it has been combined with healthcare systems and the establishment of electronic health records (EHR) to follow up on patients. This merging of technology with healthcare has allowed for more accurate EHRs that follow a patient to different healthcare facilities. Timely exchange of electronic health information (EHR) between providers is critical for aiding medical research and providing fast patient treatment. As a result, security issues and privacy problems are viewed as significant difficulties in the healthcare system. Several remote user authentication methods have been suggested. In this research, we present a feasible patient EHR migration solution for each patient. finally, each patient may securely delegate their current hospital’s information system to a hospital certification authority in order to receive migration proof that can be used to transfer their EHR to a different hospital. In addition, the proposed scheme is based on crypto-hash functions and asymmetric cryptosystems by using homomorphic cryptography. The proposed scheme carried out two exhaustive formal security proofs for the work that was provided. Using Scyther, a formal security tool, we present a secure user authentication technique in the proposed healthcare scheme that ensures security and informal analysis.